Gut microbiota: changing the disease architecture - Chaudhary, Ansh; Chaudhary, Bhupendra (International Journal of Advances in Medicine, 2020)
Gut microflora comprising of trillions of various bacteria, protozoan, virus and fungi who live as a super-complex ecosystem in human body mostly (around 70%) in gastrointestinal tract. In habitating skin, mouth, intestine and sexual organs they live as symbiotic, commensal or pathogenic organism in the human body. These gut microflora interplay with bodily metabolic, immune, endocrinal and nervous system which leads to various pathophysiological mechanism for the causation of related disorders. This altered ‘Brain gut axis’ is responsible for disorders like anxiety, depression, autism, schizoaffective or bipolar disorder and also diseases like Parkinson’s disease and multiple sclerosis.1